Decision Support System for Determining Employee Movements Using the COPRAS Method - Muhammad Dedi Irawan; Harold Situmorang; Rianto Sitanggang; Diah Sawitri (CESS (Journal of Computer Engineering, System and Science), 2023)
Employee mutation is one aspect that greatly affects the performance of employees in a company. However, employee mutations at PT. PLN (Persero) UPDL Tuntungan is still done manually, so determining the employees to be transferred takes quite a long time and the results are not optimal. The research aims to facilitate PT. PLN (Persero) UPDL Benefits in determining employee mutations in order to obtain maximum results. The stages of the research were carried out by collecting data by means of interviews then the data was inputted into the system to be calculated using the COPRAS method which was then stored into the database so that it would produce decisions with the final result ranking by the system by sorting the smallest to the largest values. The results of this study are based on the COPRAS method, namely the alternative of Ahmad Fauzy Hamdani Rahmat being the first alternative with a value of 100%. This is because Ahmad Fauzy Hamdani Rahmat's alternative meets almost all criteria ranging from age, years of service, education, position and status.